Role of Key Stakeholders in the Awareness Campaign of Right to Information (RTI) Act, Punjab - Yasin, Zaeem; Hibba Hassan; Aqdas Waheed (Journal of Peace, Development and Communication, 2021)
The study aims to check the awareness level of people towards Right to Information Act 2013 and also examines the role of key stakeholders in RTI Act Awareness Campaign. The study further investigates the barriers to effective awareness campaign of RTI Act 2013. A mix method research design has been adopted (Survey and intensive interview) to collect data. The study implies Democratic and Social Responsibility theory by Michael Laurence & Siebert, Peterson and Schramm. Purposive sampling method was used for conducting survey. Intensive interviews were taken from bureaucrats, politicians and the leaders of civil society from Pakistan. Findings showed few significant perspectives. Punjab Government enacted Right to Information as a bargain for aid from international community which reflects government’s disinterest and lack of concern for RTI’s effective implementation and awareness of general public.